Pertanggungjawaban Transportasi Daring Atas Pelayanan Konsumen dalam Prinsip Keadilan - Benedictus Klaus Brandon Arya Setya; Made Warka (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The liability of online transportation platform providers in Indonesia still raises uncertainty, particularly in determining who is responsible when consumers suffer losses. In practice, platforms often include limitation of liability clauses in standard agreements, which may weaken consumer protection and create legal uncertainty. This study aims to analyze the legal responsibility of online transportation platforms toward consumers and to examine the application of the principle of justice in the distribution of responsibility. This research uses a normative legal method with statute and conceptual approaches. The results show that platform providers cannot fully avoid responsibility, as they have control over the system and benefit from each transaction. Furthermore, limitation of liability clauses may conflict with consumer protection regulations. Therefore, clearer regulations are needed to ensure legal certainty and fairness for consumers.